2022
DOI: 10.2147/ndt.s346238
|View full text |Cite
|
Sign up to set email alerts
|

Senegenin Inhibits Aβ1-42-Induced PC12 Cells Apoptosis and Oxidative Stress via Activation of the PI3K/Akt Signaling Pathway

Abstract: Background/Aim Apoptosis and oxidative stress have been considered as key events in the pathogenesis of Alzheimer’s disease (AD). Senegenin (Sen), the major and most effective ingredient of Radix Polygalae , which has anti-apoptotic and anti-oxidative effects. The aim of this study was to investigate the anti-apoptotic and anti-oxidant effects of Sen on Aβ 1-42 -induced PC12 cells apoptosis and oxidative stress as well as its possible signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…In vitro, excessive ROS can cause oxidative stress and subsequent cell injury and apoptosis, which may be PC12 cells induced by exposure to Aβ42 [5]. The peroxidative damage of mitochondria is closely related to the high content of ROS, and MMP (ΔΨm) is an essential indicator of mitochondrial function and the apoptotic status [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, excessive ROS can cause oxidative stress and subsequent cell injury and apoptosis, which may be PC12 cells induced by exposure to Aβ42 [5]. The peroxidative damage of mitochondria is closely related to the high content of ROS, and MMP (ΔΨm) is an essential indicator of mitochondrial function and the apoptotic status [33].…”
Section: Discussionmentioning
confidence: 99%
“…Aβ induced neurotoxicity in neuronal cells has been considered as one of the crucial reasons in the development of AD [4]. The Aβ induced cytotoxicity could trigger redox impairment through producing reactive oxygen species (ROS), decreasing the mitochondrial membrane potential (ΔΨm), and inhibiting the activities of antioxidant enzymes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Sen shows unique pharmacological activity in promoting intelligence, anti-aging, antioxidant and other aspects, and also possesses cytoprotective properties in neurodegenerative disorders [12,13]. It has been previously reported that Sen was effective in inhibiting apoptosis and oxidative stress in Aβ 1−42 -induced PC12 cells [14]. Our previous study established that Sen could exert neuroprotection against H/R-induced injury via suppression apoptosis [15].…”
Section: Introductionmentioning
confidence: 88%
“…By activating the Keap-Nrf2-ARE pathway, senegenin can reduce ROS accumulation and up-regulate the expression of Nrf2 and HO-1 in a dose-dependent manner, which contributes to the reduction of oxidative stress ( Ren et al, 2022 ). In addition, senegenin can inhibit the production of PGE 2 and NO in RAW 264.7 macrophages induced by lipopolysaccharide (LPS) by suppressing MAPK/NF-κB and activating the Nrf2/HO-1 signaling pathway, and reduce inducible nitric oxide synthase (NOS) and Cyclooxygenase-2 (COX-2) gene expression ( Lv et al, 2016 ; Lu et al, 2017 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In addition, senegenin can also promote the phosphorylation of Akt ( Pi et al, 2016 ) It reveals that the PI3K/Akt signaling pathway may be involved in the neurotrophic effect of senegenin. In addition, through the PI3K/Akt signaling pathway, senegenin can also increase the ratio of P-PI3K/PI3K and P-Akt/Akt, increase cell survival in a dose-dependent manner, and reduce apoptosis ( Ren et al, 2022 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%